Unlawful attacks in combat situations: from the ICTY’s case law to the Rome Statute (2008)
Death and destruction are unavoidable effects of war and combat situations. The fact that people have been killed or injured or property has been destroyed should not encourage anyone to rush to the conclusion that war crimes have been committed. On the contrary, before reaching such a conclusion, it is necessary to carefully analyze the conduct of the person causing death, injury or damage in order to ascertain whether such conduct is consistent with international humanitarian law. Technology, law and public opinion on what is acceptable has greatly evolved since World War II. The issue of civilian damage caused in combat operations has become an important topic in public opinion since Operation Desert Storm in 1991. Public pressure to limit incidental civilian damage has notably increased following the NATO aerial campaign in Kosovo in 1999 and the subsequent conflicts in Afghanistan in 2001, Iraq in 2003 and Lebanon 2006. Unlawful Attacks in Combat Situations focuses on the manner in which unlawful attacks launched during the conduct of hostilities have been dealt with in the Rome Statute of the International Criminal Court, the international treaty which, to date, deals most comprehensively with war crimes committed in international and non-international armed conflicts, and in the case law of the International Criminal Tribunal for the Former Yugoslavia, the first international judicial body that has investigated and prosecuted crimes committed during the conduct of hostilities since World War II.